The meanings of rural community according to nature of community livelihood in Brazilian Amazonia - Vasconcellos, Ana Maria de Albuquerque; Vasconcellos Sobrinho, Mario (Interações, 2017)
The paper discusses the meanings of rural community according to nature of community livelihood in Brazilian Amazonia. Specifically, the paper stresses on the concept of community as a crucial aspect of the nature of diversity. The aim is to point out how development programmes interact and impact upon community’s livelihoods without to take into account the meaning of rural communities they assume. The research data was gathered from four focus group in the municipalities of Concórdia do Pará, São Domingos do Capim, Irituia and Mãe do Rio, in Pará State. The paper shows that the understanding of rural community is a result of cultural, social and political construction and intrinsically linked to nature of community livelihood.